Peer Influence during Adolescence: The Moderating Role of Parental Support - Mazneen Havewala; Julie C. Bowker; Kelly A. Smith; Linda Rose-Krasnor; Cathryn Booth-LaForce; Brett Laursen; Julia W. Felton; Kenneth H. Rubin (MDPI AG, 2021)
Although many studies show that peers influence the development of adolescent internalizing and externalizing difficulties, few have considered both internalizing and externalizing difficulties in the same study, and fewer have considered the contributions of parents. Using a longitudinal sample of 385 adolescents, the contributions of best friends' internalizing and externalizing difficulties (as assessed in Grade 6; G6: Mage = 13.64 years; 53% female; 40% ethnic or racial minority) were examined as they predicted subsequent adolescent internalizing and externalizing difficulties (at G8); in addition, the moderating role of both maternal and paternal support (at G6) was explored. Structural equation modelling revealed that best friend internalizing difficulties predicted decreases, but that best friend externalizing difficulties predicted increases in adolescents' externalizing difficulties over time. Significant interactions involving both maternal and paternal support revealed that the negative impact of a G6 best friend having internalizing problems on later G8 adolescent externalizing problems was stronger at low levels of maternal and paternal support. The findings highlight the complex, and interactive, influences of friends and parents on the development of internalizing and externalizing symptomatology during adolescence, and underscore the importance of targeting both sources of social influence in research and clinical work.